N-terminal-pro-brain natriuretic peptide, but not brain natriuretic peptide, is increased in patients with severe obesity - Fernandes,F. (2007)
Elevated body mass index (BMI) has been reported as a risk factor for heart failure. Prevention of heart failure through identification and management of risk factors and preclinical phases of the disease is a priority. Levels of natriuretic peptides as well as activity of their receptors have been found altered in obese persons with some conflicting results. We investigated cardiac involvement in severely obese patients by determining N-terminal-pro-brain natriuretic peptide (NT-proBNP) and brain natriuretic peptide (BNP) and attempting to correlate the levels of these peptides in serum and plasma, respectively, with BMI, duration of obesity, waist circumference, and echocardiographic parameters. Thirty-three patients with severe obesity (mean BMI: 46.39 kg/m², mean age: 39 years) were studied. The control group contained 30 healthy age-matched individuals (BMI: <25 kg/m², mean age: 43 years). The t-test and Spearman correlation were used for statistical analysis. Log-NT-proBNP was significantly higher (P = 0.003) in obese patients (mean 1.67, 95% CI: 1.50-1.83 log pg/mL) compared to controls (mean: 1.32, 95% CI: 1.17-1.47 log pg/mL). The Log-NT-proBNP concentration correlated with duration of obesity (r = 0.339, P < 0.004). No difference was detected in the Log-BNP concentration (P = 0.63) of obese patients (mean: 0.73, 95% CI: 0.46-1.00 log pg/mL) compared to controls (mean: 0.66, 95% CI: 0.51-0.81 log pg/mL). NT-proBNP, but not BNP, is increased in severely obese patients and its concentration in serum is correlated with duration of obesity. NT-proBNP may be useful as an early diagnostic tool for the detection of cardiac burden due to severe obesity.